Answer:
x-y=-2
Step-by-step explanation:
Divide both sides if the equations by 3.
(3y-3x)÷3=6÷3
y-3x÷3=2
calculate the quotient
y-x=2
multiply both sides of the equation bub -1
-1x(-x)-1y=-1x2
any expression multiplied by -1
x-1y=-1x2
any expression multiplied by 1 remains the same.
x--y=-1x2
x-y=-2
There are three options which are the square roots of 100, and those are C. -10, D. 10, and F. |10|
C: (-10)^2 = -10 * -10 = 100 (- * - = +)
D: 10 * 10 = 100
F: |10| = 10, and 10 * 10 = 100 (these brackets make a negative number positive, and a positive number stays positive)
So ur going from a smaller shape to a larger shape....means the scale factor is more then 1. The scale factor is the number that u multiply the original shape by to get the other shape.
so lets look at DE...it is 2.....and D'E' is 6
so 2 * x = 6...with ur scale factor being x
2x = 6
x = 6/2
x = 3.....so the scale factor is 3....because multiplying the original shape by 3, gives u the other shape
Answer:
The statement is true
Step-by-step explanation:
The question is as following :
is divisible by 7 and 19, true or false?
The given expression is
Take as a common
So, divided 7 =
And divided 19 =
is divisible by 7 and 19 (<u>True</u>)
Answer:
(2,-3)
Step-by-step explanation:
I am not sure if you meant the first equation to be y or -y. I solved it as y.
y = x-5 -x -3y =7
I am going to take the second equation and write it as x =
-x - 3y = 7 Give equation
-x = 3y +7 Add 3y to both sides
x = -3y-7 Multiplied each term in the equation by -1 so that x could be positive
I am going to substitute -3y-7 for x in the first equation up above
y = x - 5
y = -3y -7 - 5 Substitute -3y-7 for x
y = -3y -12 Combined -7-5
4y = -12 Added 3y to both sides
y = -3 Divided both sides by 4.
I now know that y is -3, I will plug that into x = -3y-7 to solve for x
x = -3(-3) -7
x = 9-7 A negative times a negative is a positive
x = 2